Kartini Abad 21: Analisis Pemikiran Maudy Ayunda dalam Mendorong Reformasi Pendidikan Indonesia - Keke Ayuning Tiyas Santoso; Masduki Asbari; Devona Bunga Madania (Journal of Information Systems and Management (JISMA), 2025)
This study is to explore how contemporary women, as representations of modern-day Kartini, are capable of challenging the status quo through their ideas and concrete actions, particularly in the field of education. This research employs a descriptive qualitative method using the listen-and-note technique, as data were obtained by observing verbal narratives from the YouTube channel of Gita Wirjawan, titled "Maudy Ayunda: Kartini Modern Berani Tantang Status Quo", featuring Maudy Ayunda, along with public documentation of her thoughts on the urgency of transforming Indonesia’s education system. The findings reveal that Maudy Ayunda’s perspectives on holistic education, curriculum flexibility, and digital literacy reflect the spirit of emancipation that not only advocates for women's rights but also expands the space for systemic reform in an education system that remains rigid and non-inclusive. As a figure of the modern Kartini, Maudy utilizes digital platforms to foster collective awareness of the need to shift educational paradigms. This study originates from the observation of the evolving roles of women in digital society and the growing urgency for systemic change within higher education institutions and beyond.